An alternative conformation of ERβ bound to estradiol reveals H12 in a stable antagonist position - Paulo C. T. Souza (Nature Portfolio, 2017)
Abstract The natural ligand 17β-estradiol (E2) is so far believed to induce a unique agonist-bound active conformation in the ligand binding domain (LBD) of the estrogen receptors (ERs). Both subtypes, ERα and ERβ, are transcriptionally activated in the presence of E2 with ERβ being somewhat less active than ERα under similar conditions. The molecular bases for this intriguing behavior are mainly attributed to subtype differences in the amino-terminal domain of these receptors. However, structural details that confer differences in the molecular response of ER LBDs to E2 still remain elusive. In this study, we present a new crystallographic structure of the ERβ LBD bound to E2 in which H12 assumes an alternative conformation that resembles antagonist ERs structures. Structural observations and molecular dynamics simulations jointly provide evidence that alternative ERβ H12 position could correspond to a stable conformation of the receptor under physiological pH conditions. Our findings shed light on the unexpected role of LBD in the lower functional response of ERβ subtype.